Social and Economic Mobility in the Indonesia-Timor Leste Border Area (Case Study in Motaain Region Belu Regency) - Nino, Handrianus; Seran, Remigius; Binsasi, Heribertus (LEGAL BRIEF, 2025)
This aims to study dynamic mobility social and economic communities in the Indonesia-East Timor border region with approach locality, which focuses on practices and relations daily public border in responding to national borders. With method qualitative and approach ethnographic, research This describes How identity, network social, and economic strategies constructed in room fluid and interactive borders. Research results show that the state borders are not only as entity administrative, but rather room negotiated social repetition in a way continuously by actor locals through activity cross border.